A negatively charged region within carboxy-terminal domain maintains proper CTCF DNA binding - Lian Liu; Yuanxiao Tang; Yan Zhang; Qiang Wu (iScience)
Summary: As an essential regulator of higher-order chromatin structures, CCCTC-binding factor (CTCF) is a highly conserved protein with a central DNA-binding domain of 11 tandem zinc fingers (ZFs), which are flanked by amino (N-) and carboxy (C-) terminal domains of intrinsically disordered regions. Here we report that CRISPR deletion of the entire C-terminal domain of alternating charge blocks decreases CTCF DNA binding but deletion of the C-terminal fragment of 116 amino acids results in increased CTCF DNA binding and aberrant gene regulation. Through a series of genetic targeting experiments, in conjunction with electrophoretic mobility shift assay (EMSA), circularized chromosome conformation capture (4C), qPCR, chromatin immunoprecipitation with sequencing (ChIP-seq), and assay for transposase-accessible chromatin with sequencing (ATAC-seq), we uncovered a negatively charged region (NCR) responsible for weakening CTCF DNA binding and chromatin accessibility. AlphaFold prediction suggests an autoinhibitory mechanism of CTCF via NCR as a flexible DNA mimic domain, possibly competing with DNA binding for the positively charged ZF surface area. Thus, the unstructured C-terminal domain plays an intricate role in maintaining proper CTCF-DNA interactions and 3D genome organization.